Perception of Selected Aspects of Online Learning by Czech Higher Education Students - Krpálková Krelová, Katarína; Berková, Kateřina; Krpálek, Pavel; Kubišová, Andrea (International Journal of Engineering Pedagogy (iJEP), 2022)
The study is based on an analysis of real educational processes in the period 2020-2021, when the most significant pandemic waves of Covid-19 were recorded in the Czech Republic. In relation to this, the study aims to identify the views of 968 students on the changed conditions of education and the perception of selected aspects of the transition to online learning by respondents from two higher education institutions in the Czech Republic, the first of which is focused on humanities and the second specializes in economics studies. The research is aimed at discovering students’ attitudes towards the form of distance education forced on them by the relevant circumstances, the use of individual components of distance education to support teaching originally designed for the in-person form, the level and effectiveness of the use of information technologies in online learning and the potential of hybrid learning. For a greater degree of analyticity, a combined research model based on both quantitative and qualitative research has been chosen. Aspects of online learning that could be employed as complementary tools in the full-time conventional study mode have been identified. Students of economics can better visualize the inclusion of online learning in the full-time conventional study mode. Master level students are critical of online learning. The results have been used to design and empirically validate appropriate learning strategies with reflection on current student needs.